Attitudes Toward COVID-19 Vaccination Among Young Adults in Zurich, Switzerland, September 2020 - Cesar Leos-Toro; Denis Ribeaud; Laura Bechtiger; Annekatrin Steinhoff; Amy Nivette; Aja L. Murray; Urs Hepp; Boris B. Quednow; Boris B. Quednow; Manuel P. Eisner; Manuel P. Eisner; Lilly Shanahan; et al. (Frontiers Media S.A., 2021)
Objectives: Young adults are essential to the effective mitigation of the novel coronavirus (SARS-CoV-2/COVID-19) given their tendency toward greater frequency of social interactions. Little is known about vaccine willingness during pandemics in European populations. This study examined young people's attitudes toward COVID-19 vaccines in Fall 2020.Methods: Data came from an ongoing longitudinal study's online COVID-19-focused supplement among young adults aged 22 in Zurich, Switzerland (N = 499) in September 2020. Logistic regressions examined young adults' likelihood of participating in COVID-19 immunization programs.Results: Approximately half of respondents reported being unlikely to get vaccinated against COVID-19. Compared to males, females were more likely to oppose COVID-19 vaccination (p < 0.05). In multivariate models, Sri Lankan maternal background and higher socioeconomic status were associated with a greater likelihood of getting vaccinated against COVID-19 (p < 0.05). Respondents were more likely to report a willingness to get vaccinated against COVID-19 when they perceived 1) an effective government response (p < 0.05) and 2) their information sources to be objective (p < 0.05).Conclusion: This study communicates aspects important to the development of targeted information campaigns to promote engagement in COVID-19 immunization efforts.